Analisis Kesejahteraan Kelompok Industri Tempe Di Tegal RejoDan Paulan Barat Kelurahan Paulan Kecamatan ColomaduKabupaten Karanganyar - qodri, lailatul; , Dr. Priyono, M.Si; , Dra. Umrotun, M.Si (2015)
This research was conducted at Tegal Rejo and Paulan West Village District of Colomadu Paulan Karanganyar. This study aimed to analyze the soybean industry and analyze welfare tempe industry groups in Tegal Rejo and Paulan West Village District Colomadu Paulan of Karanganyar. The method used in this study is a survey method using secondary data obtained from the BKKBN (2014) and primary data obtained through interviews, observation, and recording with the Tegal Rejo and Paulan West Village District of Colomadu Paulan Karanganyar. Geography approach used in this study is the spatial approach. The analysis used in this study is a SWOT analysis (Strengths Weaknesses Opportunities Threats). Results of research on the welfare of Tegal Rejo and Paulan West showed the highest initial capital in Tegal Rejo Rp.1.310.000 ie (60%) 6 Paulan respondents and in the west (84%) 5 respondents, the largest source of capital in Tegal Rejo derived from its own capital ie (70%) 7 respondents and Paulan West (50%) 3 respondents, the origin of most workers in Tegal Rejo come from every village each ie (50%) and Paulan West 5 respondents (84%) 5 respenden, the amount of power Most work in Tegal Rejo 1-5 people are (100%) 10 respondents and Paulan West (83%) 5 respondents, most types tegnologi in Tegal Rejo kind of modern technology (80%) 8 respondents and in Paulan West (100%) 6 respondents, the origin of the raw materials in Tegal Rejo from outside Karanganyar ie (50%) 5 respondents and Paulan West (50%) 3 respondents, the type of production in Tegal Rejo tempeh wrap leaf types (80%) 8 respondents and Paulan West (85 %) 5 respondents, the marketing area Tegal rejo out Karanganyar (30%) and Paulan West 3 respondents (41%) 3 respondents, education level in Tegal Rejo high school (90%) 9 respondents and Paulan West (83%) 5 respondents , facilities in Tegal Rejo fan (90%) 9 respondents and Paulan West (100%) 6 respondents, revenue in Tegal Rejo Rp. 1.500.000- Rp. Namely 2,000,000 (70%) 7 respondents and Paulan West (100%) 6 respondents, the ownership of land / house in Tegal Rejo private property (50%) and Paulan West 5 respondents (83%) 5 respondents, vehicle ownership in Tegal Rejo in the form of a car (80%) 8 respondents and Paulan West (83%) 5 respondents selected health facilities in Tegal Rejo are doctors (30%) 3 respondents and Paulan West (49%) 3 respondents, eating tempe whole industry entrepreneurs have ie 3x daily diet (100%) 16 respondents, selected food consumption in Tegal Rejo of meat that (40%) 4 respondents and Paul's West (34%) of 2 respondents while ownership of livestock for Tegal Rejo area in the form of chickens and goats ie (30%) of respondents for Area 3 West Paulan no respondents who have cattle. Conclusions based on the results of the analysis of the welfare group tempe industry in Tegal Rejo and Paulan West Village District of Colornadu Paulan Karanganyar prosperous category.